Effect of plasma-enhanced atomic layer deposited YSZ inter-layer on cathode interface of GDC electrolyte in thin film solid oxide fuel cells. (December 2019) - Lee, Sanghoon; Lee, Yeageun; Park, Joonho; Yu, Wonjong; Cho, Gu Young; Kim, Yusung; Cha, Suk Won
Abstract: We have fabricated thin film-solid oxide fuel cells (TF-SOFCs) with tri-layer electrolytes, which are composed of YSZ deposited by sputtering, YSZ deposited by plasma enhanced atomic layer deposition (PEALD), and GDC deposited by sputtering. Then, we have investigated the effects of the PEALD YSZ on the GDC layer and the whole cell. Open circuit voltages (OCVs) and peak power densities of the cells kept being enhanced as the thickness of the PEALD YSZ layer increases. The 1000 cycle of PEALD YSZ deposited TF-SOFC exhibited 214 mW/cm 2 of peak power density, while TF-SOFC without PEALD YSZ inter-layer showed 124 mW/cm 2, almost half of that of the 1000 cycle sample. FE-SEM images and AFM analysis of the top surface of GDC electrolytes sustain this phenomenon. As the PEALD YSZ inter-layer thickness increases, the top surface of GDC electrolyte become rough, with pin-holes disappeared, and the grain size of GDC electrolyte grew smaller. As a result, the improved quality of the electrolytes enhanced OCV and smaller grain size of the electrolytes caused better catalytic activity on the electrolyte-cathode interface, leading to lower faradaic impedances in electrochemical impedance spectroscopy (EIS). Highlights: Sputtering and Plasma enhanced atomic layer deposition (PEALD) were used to deposit multi-layered electrolyte. The effect of PEALD YSZ inter-layer on the cathode interface of GDC electrolyte was studied. Thicker PEALD YSZ inter-layer enhances the overall SOFC performance. The causes of performance improvement were investigated via FE-SEM and AFM.